Simulation of single phase hybrid active power filter to reduce harmonic current in non linear load / Azizul Mohamad @ Embong - Mohamad @ Embong, Azizul (2010)
The past several years have seen a rapid increase of power electronics-based loads connected to the distribution system. These types of loads draw non sinusoidal current from the mains, degrading the power quality by causing harmonic distortion. This thesis proposes a single-phase hybrid active power. The proposed topology interconnects a passive band-pass filter in series with a shunt active power filter. The uniqueness of the proposed topology is the fact that it improves the harmonic filtering performance of a basic hybrid active power filter. The compensation current reference for the proposed topology is obtained by using the PWM controller techniques. This work describes the design of circuit topology, control system, combination of passive and active filter and control circuit to provide carrier signal. The system is verified by simulation using MATLAB/ Simulink simulation package. The simulation results show that the system effectively reduces the total harmonic distortion of the source current from 360.98 % to 2.3 %.The operating principles and simulation result are present.